ACTR-71. PHASE 1/2 STUDY OF DIANHYDROGALACTITOL (VAL-083) WITH RADIATION THERAPY IN PATIENTS WITH NEWLY DIAGNOSED, MGMT-UNMETHYLATED GLIOBLASTOMA. (5th November 2018) - Chen, Zhong-ping; Guo, Chengcheng; Bacha, Jeffrey; Steino, Anne; Langlands, John; Kwan, Claire; Kanekal, Sarath; Schwartz, Richard; Lopez, Lorena; Brown, Dennis
Abstract: Glioblastoma (GBM) is the most common and aggressive primary brain cancer. Current standard-of-care includes surgery followed by chemo-radiation and temozolomide. An unmethylated promoter for O6-methylguanine-DNA-methyltransferase (MGMT) is a validated biomarker for temozolomide-resistance and is strongly correlated with poor outcomes. Unmethylated MGMT represents the majority of newly diagnosed GBM tumors. VAL-083 is a first-in-class bi-functional DNA-targeting agent that has shown activity against GBM in NCI-sponsored clinical trials both as single agent and in combination with radiotherapy. VAL-083 induces interstrand cross-links at N7-guanine, leading to DNA double-strand breaks and cell-death. VAL-083s unique mechanism-of-action circumvents MGMT-mediated chemoresistance, and it has demonstrated cytotoxicity in MGMT-unmethylated GBM cell-lines, cancer stem cells (CSCs) and in vivo models. Furthermore, VAL-083 acts as a radiosensitizer in GBM CSCs and non-CSCs. We completed a dose-escalation trial of VAL-083 in recurrent GBM, and a generally well-tolerated dosing regimen was selected for further clinical development. The present trial is an ongoing open-label, biomarker-driven, Phase 1/2 study to evaluate the tolerability and efficacy of VAL-083 in combination with radiotherapy in newly diagnosed MGMT-unmethylated GBM patients. A treatment regimen, consisting of a 6-week induction period of VAL-083 and concurrent radiation (2 Gy daily, 5 days/week) followed by up to 24 weeks of maintenance therapy with single-agent VAL-083, is being evaluated. The study is being conducted in two parts: 1) a dose-escalation part (20, 30, and 40mg/m2/day IV infusion on days 1, 2, 3 of a 21-day cycle) in up to 10 patients; 2) an expansion part in up to 20 additional patients at the determined well-tolerated dose. Tumor response will be assessed by MRI, according to RANO criteria. Efficacy endpoints include progression-free survival (PFS) and overall survival (OS). Additional endpoints include safety evaluations and pharmacokinetic assessments of plasma and CSF samples. Enrollment and safety data update will be provided at the meeting. Clinicaltrials.gov identifier: NCT03050736.